Numerical study of flow boiling in an intermediate-scale vertical tube under low heat flux. (5th May 2019) - Yin, Xuan; Tian, Yongsheng; Zhou, Dan; Wang, Naihua
Highlights: A flow boiling model in an intermediate-scale vertical tube is constructed. The characteristics of the flow pattern rely on the height of the tube and low heat flux. The dynamic characteristics of flow boiling are analyzed. The heat transfer is enhanced with the increase in height. Abstract: This article numerically investigates the flow boiling behavior in an intermediate-scale vertical tube for an evaporator of a separated type heat pipe. In this study, the volume of fluid (VOF) model and the vapor-liquid phase change model (according to a user defined function) are used to build a numerical model of a single vertical tube with a 50 mm inner diameter and 5000 mm length for simulating the flow regime. Different two-phase flow characteristics are present in the vertical tube working in low heat flux. We analyze the bubble movement and classify the two-phase flow regimes in an intermediate-scale vertical tube into four patterns: bubbly flow, cap flow, slug flow and churn flow. Furthermore, the local characteristic of boiling heat transfer along the tube and the effect of the bubble regimes on the heat transfer are studied. The results indicate that saturated nucleate boiling is the dominant boiling form under low heat flux.